2022
DOI: 10.23887/jisd.v6i2.44889
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Metacognition on Elementary School Students’ Problem-Solving Skills in Science Learning

Abstract: The concept of education at the basic education level plays an important role in character building and students' cognitive, affective, and psychomotor development. Through science learning, it is hoped that students will not only know the concept, but are directed to be able to solve problems in the surrounding environment. However, the facts show that students in elementary schools still have difficulty solving analytical problems in science learning. This study aims to analyze the effect of metacognition on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
10
0
6
Order By: Relevance
“…"Creative thinking has so far received little attention in education, especially in school learning which is still focused on acquiring knowledge, memory, and reasoning; with the implementation of the PjBL model through making a herbarium; students are involved in analyzing problems, then exploring, collecting information, interpretation, and assessment of working on projects related to the problems studied (Elvianasti & Kartikawati, 2022) so that this learning allows students to develop their creativity in designing and making projects that can be used to solve" problems (Fauzia & Kelana, 2020) determining that this project is included in the fluency category because students are given several stimulus questions to determine the project for the second stage of designing project steps. In this stage, the aspect of creative thinking that is stimulated is the ability of students to think flexibly and bring out original traits.…”
Section: Graph 1 Pjbl Learning Percentage Resultsmentioning
confidence: 99%
“…"Creative thinking has so far received little attention in education, especially in school learning which is still focused on acquiring knowledge, memory, and reasoning; with the implementation of the PjBL model through making a herbarium; students are involved in analyzing problems, then exploring, collecting information, interpretation, and assessment of working on projects related to the problems studied (Elvianasti & Kartikawati, 2022) so that this learning allows students to develop their creativity in designing and making projects that can be used to solve" problems (Fauzia & Kelana, 2020) determining that this project is included in the fluency category because students are given several stimulus questions to determine the project for the second stage of designing project steps. In this stage, the aspect of creative thinking that is stimulated is the ability of students to think flexibly and bring out original traits.…”
Section: Graph 1 Pjbl Learning Percentage Resultsmentioning
confidence: 99%
“…Despite the majority of research on PBL’s positive effects being conducted with students from higher education as participants (Verstegen et al, 2016 ), studies also identified positive learning results from K-12 learners worldwide (i.e., Kokotsaki et al, 2016 ). In terms of the learning experience, implementing PBL can improve the quality of learning for elementary students (Fauzia & Kelana, 2021 ), yield higher learning outcomes (Amini et al, 2019 ), and increase the affective connection (Virtue & Hinnant-Crawford, 2019 ). Implementing PBL improves students' academic achievement and knowledge retention (Al-Balushi & Al-Aamri, 2014 ), increasing the student's science process skills and cognitive learning outcomes (Nasir et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pola Interaksi dalam Menumbuhkan Scientific Attitude (Diadaptasi dari Buku Teori Belajar dan Pengukurannya) Dalam ikhtisar pada www.bantenprov.go.id mengungkapkan bahwa Pemerintah provinsi (Pemprov) Banten secara sadar mendorong terbentuknya peserta didik teladan dan memiliki scientific attitude baik. Sebagaimana tertuang dalam visi-misi pembangunan daerah yakni meningkatkan akses dan pemerataan pendidikan berkualitas (Fauzia & Kelana, 2020). Suatu perhatian besar telah diberikan Pemprov Banten, maka menjadi harapan kedepannya peserta didik memiliki scientific attitude yang tinggi untuk menopang pencapaian belajar.…”
Section: Gambarunclassified